2020
DOI: 10.1371/journal.pone.0224251
|View full text |Cite
|
Sign up to set email alerts
|

Decorin inhibits glucose-induced lens epithelial cell apoptosis via suppressing p22phox-p38 MAPK signaling pathway

Abstract: To determine the effect of decorin on oxidative stress and apoptosis of human lens epithelial (HLE) cells under high glucose condition. Methods HLE cell line (HLEB3) was incubated in normal glucose (5.5 mM) or high glucose (60 mM) medium. Decorin (50 nM) was applied 2 hours before high glucose medium was added. Apoptosis detection was executed by flow cytometry and western blotting (analysis of bcl-2 and bax). Oxidative stress level was measured by the generation of reactive oxygen species (ROS), glutathione p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…DCN is a member of the SLRP family and is widely located in various connective tissues, serving as a vital regulator in the physiological processes [ 21 ]. Previous study reported that DCN could protect against oxidative stress in glucose-induced lens epithelial cell apoptosis [ 23 ]. In the kidney and neuronal tissues, the administration of DCN intraperitoneally ameliorated the MDA level and increased the SOD level [ 27 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DCN is a member of the SLRP family and is widely located in various connective tissues, serving as a vital regulator in the physiological processes [ 21 ]. Previous study reported that DCN could protect against oxidative stress in glucose-induced lens epithelial cell apoptosis [ 23 ]. In the kidney and neuronal tissues, the administration of DCN intraperitoneally ameliorated the MDA level and increased the SOD level [ 27 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that autophagy activators such as melatonin and rapamycin showed great potential in AMD treatment [ 18 , 19 ]. Among these activators, decorin (DCN) has been shown to promote autophagy in various cells including endothelial, nucleus pulposus, and breast carcinoma cells [ 20 23 ]. DCN, identified as a class I small leucine-rich proteoglycan (SLRP), localizes to the cornea, skin, and other connective tissue and serves as a regulator of various cellular function by fettering to extracellular matrix molecules or through cell receptors [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The apoptosis of lens epithelial cells is a common cellular basis for the occurrence and development of ARC [23]. A number of common apoptosis pathways such as p53, MAPK, and TGF-β signaling pathways are closely related to the occurrence of ARC, and several appear in our top 20 KEGG pathways [24][25][26]. Some genes of interest in these pathways include DUSP1, ID1, and CAV2, which all function in multiple signaling pathways [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Third, in HLEB3 cells, decorin inhibits rac1 expression and p38 MAPK activation under conditions of high-glucose. In a prior study conducted by our lab, we explored the effect of decorin inhibition on the p22 phox -p38 MAPK pathway [23]. Results from that study showed that decorin protect HLEB cells by suppressing the p22phox-p38 MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%